PERBAIKAN KUALITAS PEMBELAJARAN DAN HASIL BELAJAR SISWA DENGAN MODEL LEARNING CYCLE COOPERATIVE 5 FASE DALAM PENGAJARAN KIMIA - Esti Munafifah; Agus Basir Ali Akbar (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2015)
The objective of this study is to see learning process using LCC model for chemistry course. The study used classroom action research with three cycles each of which implements planning, acting, observing and reflection. Subject of the study was 40 students of grade 8E of MTsN Blitar in the academic year 2009/2010. The findings of the study are as follows: (1) Cycle I: students participation 62.5%, mean score of worksheet 60, mean score of quiz 41,7, and mastery learning 3 students; (2) Cycle II: students participation 86.6%, mean score of worksheet 81, mean score of quiz 72.38, and mastery learning 26 students; (3) Cycle III: students participation 100%, mean score of worksheet 89, mean score of quiz 72.44, and mastery learning 39 students.